Health-related life cycle risks and public insurance - Daniel Kemptner (Journal of Health Economics, 2019)
Based on a dynamic life cycle model, this study analyzes health-related risks of consumption and old-age poverty. The model allows for health effects on employment risks, on productivity, on longevity, the correlation between health risks, productivity and preferences, and the financial incentives of the German public insurance schemes. The estimation uses data on male employees and an extended expectation-maximization algorithm. Simulations suggest that health shocks induce average losses in annual consumption of about 10% and account for more than two-thirds of the cases of old-age poverty. Annuity markets that account for differences in the longevity risk by health status can effectively reduce the consumption risks, but only slightly decrease old-age poverty. A policy analysis of minimum pension benefits indicates that a means test mitigates the associated moral hazard problem substantially.
Keywords: C61; I14; J22; J26; 330; Dynamic programming; Discrete choice; Health; Employment; Early retirement; Consumption; Tax and transfer system